2021
DOI: 10.1111/aji.13431
|View full text |Cite
|
Sign up to set email alerts
|

Association of FOXP3 rs3761548 polymorphism and its reduced expression with unexplained recurrent spontaneous abortions: A South Indian study

Abstract: Problem: Fork Head Box Protein 3 (FOXP3) is an X‐linked gene, codes for a master transcription regulatory protein that controls the development and function of immunosuppressive T regulatory (Treg) cells. They are crucial mediators of maternal foetal tolerance and successful pregnancy outcome. The aim of the study is to evaluate the association of FOXP3 rs3761548 functional polymorphism and to assess the serum concentrations of full‐length FOXP3 protein in Unexplained Recurrent Spontaneous Abortions (URSA) pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
(46 reference statements)
1
3
0
Order By: Relevance
“…Decrease of CD4 + CD25 + and FoxP3 + Treg cells has been reported in decidua and/or peripheral blood of women with RSA and missed abortion. The expression of full-length FOXP3 protein was reduced in women with RSA compared to control group [37]. Our ndings were in line with previous studies because we demonstrated the reduction of CD4 + CD25 bright T-cells, FoxP3 expression and TGF-β concentration in peripheral blood of women with RSA .However, some studies have also reported that no signi cant difference is observed between the patient and control groups .…”
Section: Discussionsupporting
confidence: 91%
“…Decrease of CD4 + CD25 + and FoxP3 + Treg cells has been reported in decidua and/or peripheral blood of women with RSA and missed abortion. The expression of full-length FOXP3 protein was reduced in women with RSA compared to control group [37]. Our ndings were in line with previous studies because we demonstrated the reduction of CD4 + CD25 bright T-cells, FoxP3 expression and TGF-β concentration in peripheral blood of women with RSA .However, some studies have also reported that no signi cant difference is observed between the patient and control groups .…”
Section: Discussionsupporting
confidence: 91%
“…In conclusion, our study indicates that variation in FOXP3 gene is associated with a reduced risk of RPL among Lebanese women. The study has notable strengths, specifically because idiopathic RPL cases and control women were ethnically juxtaposed, thus reducing the contribution of ethnicity, which is of concern in view of the ethnic structure of the contemporary Lebanese population, 41–43 and in the robust statistical analysis, with adjustment for some confounding variables. Our study has also some limitations in that we did not evaluate Foxp3 protein concentrations against the studied variants.…”
Section: Discussionmentioning
confidence: 99%
“…FOXP3 rs3761548 polymorphism (−3279 C > A) is associated with a reduced expression of full-length FOXP3 protein in patients with unexplained RSA [ 28 ], and rs3761548 A/C polymorphism might be a significant risk factor for RPL [ 51 , 52 ]. Additionally, a potential relationship between further variants of FOXP3 rs5902434, rs2232365 and rs2294021 and idiopathic recurrent miscarriage was confirmed [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fork head box protein 3 (FOXP3) is an X-linked gene that codes a master transcription regulatory protein controlling the development and function of immunosuppressive T regulatory cells. These cells are key mediators of maternal fetal tolerance [ 28 ]. A decrease in T regulatory cells in peripheral blood and decidua leads to a decrease in FOXP3 gene expression, which affects the development and function of CD4+ CD25+ T regulatory cells [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%